The density and diversity of plant-parasitic nematodes associated with maize rhizosphere in Malakaji Highland, South Sulawesi, Indonesia - Hishar Mirsam; AMRAN MUIS; NURNINA NONCI (Society for Indonesian Biodiversity, 2020)
Abstract. Mirsam H, Muis A, Nonci N. 2020. The density and diversity of plant-parasitic nematodes associated with maize rhizosphere in Malakaji Highland, South Sulawesi, Indonesia. Biodiversitas 21: 2654-2661. Plant-parasitic nematodes (PPNs) are one of the important pathogens, especially in tropical countries, including Indonesia. Nematodes can cause high yield losses and economic damage if not managed properly. This study aims to analyze PPN density in the vegetative phase of maize in the Malakaji Highland Gowa Regency, South Sulawesi. The sampling method was a diagonal sampling technique, done by taking samples at points along a diagonal line, which were the middle and fourth corners of the maize crop. Nematode extraction was done by the modified Baerman method. The density of parasitic nematode communities counted was absolute community density, relative community density, absolute frequency, relative frequency, frequency of all nematodes, and dominance values. Nematode identification was based on morphological characters. The highest PPNs density was found in two weeks old of maize planted area where the absolute community density reaching 618 and the dominance value of 61.80%. Age of maize plants is negatively correlated with PPNs community with a regression coefficient of (-3.85). So that it can be assumed that the older the age of maize plants, the lower the amount of PPNs. Five genera of plant-parasitic nematodes associated with the rhizosphere of maize plants were found, namely Helicotylenchus, Pratylenchus, Haplolaimus, Longidorus, and Xiphinema. In addition to parasitic nematodes, non-parasitic nematodes were also identified as having no stylet, namely Campydoroides, Mononchus, and Rhabditis.